2013
DOI: 10.4161/cc.23822
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-14 Pkl1 targets γ-tubulin for release from the γ-tubulin ring complex (γ-TuRC)‬‬‬‬‬‬‬

Abstract: The γ-tubulin ring complex (γ-TuRC) is a key part of microtubule-organizing centers (MTOCs) that control microtubule polarity, organization and dynamics in eukaryotes. Understanding regulatory mechanisms of γ-TuRC function is of fundamental importance, as this complex is central to many cellular processes, including chromosome segregation, fertility, neural development, T-cell cytotoxicity and respiration. The fission yeast microtubule motor kinesin-14 Pkl1 regulates mitosis by binding to the γ-tubulin small c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 33 publications
1
43
0
Order By: Relevance
“…KIFC5A has an additional ATP-independent microtubule-binding domain (Zhang and Sperry, 2004) and Ncd has a positively charged sequence in its tail domain that tethers it to the C-terminal E-hook of tubulin . Mouse KIFC1 has tail domain sequences that target it to membrane-bound organelles (Zhang and Sperry, 2004); the tail domain of Pkl1 direct it to γ-tubulin (Olmsted et al, 2013(Olmsted et al, , 2014. Additional studies in which chimeric kinesin-14 proteins of human HSET, Drosophila Ncd and fission yeast Pkl1 were generated also support this paradigm and confirm that tail domain sequences orchestrate function (Simeonov et al, 2009).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…KIFC5A has an additional ATP-independent microtubule-binding domain (Zhang and Sperry, 2004) and Ncd has a positively charged sequence in its tail domain that tethers it to the C-terminal E-hook of tubulin . Mouse KIFC1 has tail domain sequences that target it to membrane-bound organelles (Zhang and Sperry, 2004); the tail domain of Pkl1 direct it to γ-tubulin (Olmsted et al, 2013(Olmsted et al, , 2014. Additional studies in which chimeric kinesin-14 proteins of human HSET, Drosophila Ncd and fission yeast Pkl1 were generated also support this paradigm and confirm that tail domain sequences orchestrate function (Simeonov et al, 2009).…”
Section: Introductionmentioning
confidence: 58%
“…An exception to this is Pkl1, for which the tail domain was shown to be able to regulate nucleation without the motor domain in vitro and in vivo (Fig. 1B), and to do so in yeast and human cells (Olmsted et al, 2013(Olmsted et al, , 2014. Microtubule-dependent D. melanogaster Ncd motors have been shown to localize to parallel microtubules where they exert their movement into the opposite direction, thus creating a 'tug-of-war' effect.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, S. pombe kinesin-14 Pkl1 promoted severing of γ-tubulin-anchored microtubules from the centrosome, which led the authors to suggest that microtubules released from the spindle poles contributed to central spindle organization. 6 We found that the longer and wider central bridges in DN-KIFC3 cells contained more microtubules that extended beyond the border of the central bridge than those in WT-KIFC3-expressing cells (Fig. 6A).…”
Section: Resultsmentioning
confidence: 83%
“…22 Pkl1 and HSET, by contrast, appeared to bind via microtubule-nucleating factors (γ-tubulin and augmin) that were associated with microtubule minus-ends. 3,6 To determine whether KIFC3 likewise tracked with moving microtubule ends, we examined mCherry-KIFC3 localization relative to growing microtubules in MDCK cells during the recovery from microtubule depolymerization by nocodazole. In these cells, microtubules are nucleated at the centrosome but released and captured elsewhere to give rise to the characteristic non-centrosomal microtubule organization of polarized epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation